Combining a 9-month tailored physical exercise program with osimertinib and denosumab in a patient affected by advanced NSCLC with multiple osteolytic bone lesions: A case report - Anita Borsati; Christian Ciurnelli; Lorenzo Belluomini; Marco Sposito; Jessica Insolda; Linda Toniolo; Ilaria Trestini; Daniela Tregnago; Michele Milella; Federico Schena; Sara Pilotto; Alice Avancini (Heliyon)
A 55-year-old female patient affected by an EGFR mutant NSCLC with multiple lytic bone metastases and two prior pathological fractures, undergoing treatment with osimertinib and denosumab, participated in a 9-month physical exercise program. The exercise program was performed twice a week and consisted of aerobic and strength training. Aerobic training was composed of moderate-intensity continuous training for the first 3 months and then high-intensity interval training. Strength training was performed through body-weight/elastic band exercises for the first 6 months and isotonic machines from months 6–9. Assessments, performed every 3 months, included physical fitness parameters, such as functional capacity, muscle strength, anthropometric measures, body composition, and quality of life. Functional capacity progressively improved by 80 m at month 6 and slightly decreased by 22 m at month 9. At the end of the intervention, grip strength increased in both arms, whereas the body composition showed a progressive decrease in fat mass (−3.39 kg) and an increase in muscle mass (+3.89 kg) until month 6 and then stabilization. Quality of life exhibits a great improvement in the first 3 months, especially in the physical role, emotional functioning, fatigue, pain, dyspnoea, insomnia, appetite loss, constipation, and diarrhea, and then maintained with little variations. This case suggests that a highly structured physical exercise program may be feasible, safe, and effective in patients with lung cancer and bone metastases if performed under the supervision of trained experts.